Educate to be human - Beretta Piccoli, Raffaele (Swiss Journal of Educational Research, 2020)
The article begins with an analysis of the learning experience focused on the following essential elements: relationships, freedom, intellect and emotions. Education is then defined as accompanying the learner towards a more deeply human experience of reality. This definition requires judging the conceptual distinction between education and instruction as reductive. Instruction is, in fact, itself educating for the method, which teaches you to confront your limits and favors being open-minded. As for the content, education makes the experience of reality have a greater awareness. In this process, educating to values is essential. This subject is studied in the second part of the article with a didactic proposal of education for democratic citizenship.